Characteristics analysis of integrated science question items with the rasch model - Yamtinah, Sri; Ashadi, Ashadi; Mulyani, Bakti; Utami, Budi; Kristyasari, Marantika Lia (Education and Development Research, 2023)
This study aims to analyze the characteristics of the Integrated Science question item. This is quantitative descriptive research. The research subjects were 90 students of class VIII Junior High School in the high, medium, and low categories in Surakarta City. The characteristics of the items were analyzed using the Winstep program with the Rasch Model. Based on data analysis, the results obtained are: 1) the validity of conformity level of the items is valid; 2) the reliability value of the students was 0,79 which was sufficient, the reliability of the items was 0,93 which was very good, and the reliability between the students and the items (Alpha Cronbach) was 0,81 which was very good; 3) the value of separation item > value separation of students; 4) the distribution of the difficulty level of the questions is generally in the medium category; and 5) the difference power of the questions in the very good category is 35%, 25% in the good, 30% in the moderate, and 10% in the unable to distinguish category. Thus, it can be concluded that the analysis of the characteristics of the Integrated Science question items using the Rasch Model is considered good.